2020
DOI: 10.1016/j.chaos.2020.110210
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal estimation of the daily cases of COVID-19 in worldwide using random forest machine learning algorithm

Abstract: Highlights Daily number of COVID-19 cases was estimated by the random forest method. Case estimates by random forest were mapped and compared to actual data. Random forest performed well in estimating the number of cases in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(79 citation statements)
references
References 47 publications
2
73
0
4
Order By: Relevance
“…Fanelli and Piazza [6] analyzed the temporal dynamics of the coronavirus disease 2019 outbreak in China, Italy and France. Yesilkanat [20] estimated the near future case numbers for 190 countries in the world using random forest algorithm. Sahin and Sahin [12] estimated the cumulative cases of COVID-19 using fractional nonlinear grey Bernoulli model.…”
Section: Introductionmentioning
confidence: 99%
“…Fanelli and Piazza [6] analyzed the temporal dynamics of the coronavirus disease 2019 outbreak in China, Italy and France. Yesilkanat [20] estimated the near future case numbers for 190 countries in the world using random forest algorithm. Sahin and Sahin [12] estimated the cumulative cases of COVID-19 using fractional nonlinear grey Bernoulli model.…”
Section: Introductionmentioning
confidence: 99%
“…A search, on the same date, on for studies targeting the COVID condition showed more than 3100 registered studies [ 2 , 3 ]. This disease has affected the whole world with a large number of studies and review articles appearing about different aspects of this disease: possible symptoms and treatments [ 4 , 5 , 6 , 7 , 8 , 9 ], technological tools to combat the virus [ 10 , 11 , 12 , 13 ], epidemiological models of virus transmission [ 14 , 15 , 16 ], the detection of fake news related to COVID-19 [ 17 , 18 ], etc. This huge, ever-growing amount of work reflects the need to gather knowledge about this virus in all possible ways.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a machine learning based random forest model has been used to forecast the number of COVID-19 cases with a mean correlation coefficient R 2 of 0.914. 22…”
Section: Resultsmentioning
confidence: 99%